Does “swapping” maize (Zea mays L.) inbred parents affect hybrid grain yield? - a seed production research case study - Patne, Nagesh; Takalkar, Satish Ashok; Mohan, Sagala Murali; Naidu, Pulime Bhaskara; Kanawade, Dinesh G.; Mandal, Shyam S.; Vivek, Bindiganavile Sampath (Frontiers Media, 2024)
Maize (Zea mays L.) is a globally important crop, thriving across diverse environments. Breeding maize inbreds with good combining ability for stable yields under both optimal and stress-prone conditions has been successful. However, to achieve commercial success and impact, seed producibility factors which include female and male parent flowering synchronization and seed parent yield, need to be considered in the early stages of the hybrid development process. In this study, hybrids and their reciprocals were compared through a paired T-test to ascertain if F1 performance would be affected by switching (swapping) the roles of the seed and pollen parents. While significant differences were found for grain yield, anthesis days, anthesis silking interval, plant height, ear height, and the number of ears per plant for each group of hybrids and reciprocal crosses, no significant differences were found for hybrids vs. the reciprocals for all of the traits evaluated. This indicated that swapping the roles of female and male parents in successful hybrid combinations does not affect hybrid performance.